Waste to wellness: Exploring the prebiotic potential of fruits and vegetable by-products for probiotic-enriched functional foods, Lactobacillus pentosus A6 - E. Saimen; M. M. Benedict; N. Abd Rahman; Hartinie Marbawi; Jualang Azlan Gansau; Mohd Khalizan Sabullah; Roslina Jawan (IOP Publishing Ltd., 2025)
Prebiotics are indigestible dietary fibers that enhance the host's health by encouraging the growth and activity of particular bacteria in the colon. Incorporating agricultural by-products as prebiotics into human diets is an effective way to contribute to both environmental conservation and personal well-being. Therefore, this study aims to evaluate the growth of probiotic lactic acid bacterium, Lactobacillus pentosus A6 with the presence of various types and concentrations of freeze-dried fruits (watermelon rind, melon rind, mango peel, jackfruit peel and sweet potato peel) and vegetables (cabbage, garlic chives, bitter bean peel, pumpkin peel, and seaweed) by-products at concentration of 1.0 - 2.5% (w/v), respectively. The results obtained in this study revealed that the growth of L. pentosus A6 was improved with the addition of prebiotics into the culture media. Moreover, all treatments supplemented with vegetable-by products exhibited higher viable count as compared to fruit-by products. The preference of L. pentosus A6 towards vegetables-by products was pumpkin peel, bitter bean peel, garlic chives, cabbage, and seaweed. The highest viable cells among the vegetables and fruit by-products were recorded at 2.0% (w/v) of pumpkin peel (9.47 x 1011 CFU/mL) with final pH value of 5.07 (concentration of lactic acid: 0.17) and 1.5% (w/v) of watermelon rinds (4.20 x 1010 CFU/mL) final pH 5.06 (concentration of lactic acid: 0.06), respectively. The symbiotic relationship between prebiotics and probiotics underlines the importance of selecting appropriate prebiotic sources to support the growth, the production of bioactive compounds, and the overall effectiveness of probiotic bacteria.